Coming of age in the Afro-Latin American novel : Blackness, religion, immigration - Wasserman, Bonnie S., 1966- (Rochester studies in African history and the diaspora., 2022)
"This book is the first study of recent coming-of-age novels from Brazil and the Spanish-speaking Caribbean. I investigate the divide in Afro-Latin American research that usually favors either Hispanic-America or Brazil, but not both. I argue that contemporary novelists have adapted the coming-of-age novel to explore central themes in the Afro-Latin American experience such as Blackness, African religions and folkloric traditions, and immigration. While there is no firm consensus on the term Blackness, scholars typically use the term to describe the social, cultural, and historical experience of Afro-descendants in the diaspora. The Afro-Latin American bildungsromans examined in this study include a number of religions such as Catholicism, Spiritism, and syncretic folk religions as well as Santería and Umbanda reflecting the variety of beliefs in Latin America. I have found that young people turn to religions and spiritual traditions in time of need. Going on a journey as part of one's personal development is one of the central themes of many bildungsroman, and this pertains too in Afro-Latin American novels. Caribbean characters are depicted as immigrating to the United States whereas few Brazilians have enough resources to travel to North America and instead move to larger cities within their own country"--